Papers - Determination of the Alkali-soluble Ulmins in Coal (With Discussion) - Edgar Stansfield; K. C. Gilbart (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1932)
When plants decay in a peat bog the woody parts form a brown pasty mass, or peat muck, largely soluble in alkalis. This brown matter has been termed "ulmin." The same material, but commonly black in color, is found in coal, and there is evidence of the similarity between the material forming the main bulk of the coal and the bulk of the more recently decayed material in peat bogs. The more recent or low-rank coals, such as lignite, little removed from the peat stage, contain notable percentages of alkali-soluble ulmins, but the percentage decreases with increased degree of coalification and is negligible in bituminous or higher rank coals. The determination of the alkali-soluble ulmins in any coal gives, therefore, an indication of its degree of coalification or rank. Coals which contain few or no ulmins soluble in alkalis do contain ulmins which can be rendered soluble by oxidation. The higher the rank of the coal, the more difficult it is to oxidize the insoluble ulmins and make them soluble. High-rank coals can be differentiated by oxidation tests on the insoluble ulmins; but low-rank coals can be characterized by both their soluble and insoluble ulmins. This paper deals with the determination and significance of the alkali-soluble ulmins present as such in the coal. The chemical nature and composition of ulmins are not discussed. Review of Literature The history of the study of ulmin is well given by Stopes and Wheeler.' The action of potash on coal has long been known, as Braconnot in 1819 distinguished between lignites and bituminous coals by stating that the former gave colored solutions with potash. Later the intensity of color was used to give a fuller differentiation. Hoffman2 distinguished between lignites and lignitic coals by the darker color given by the